(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article is devoted to the study of key issues related to improving the financing of investment activity in joint stock companies. Investment activity is considered as a crucial factor in ensuring sustainable economic growth, modernization of production, and enhancement of corporate competitiveness. The article examines the theoretical foundations of investment activity, forms and sources of its financing, as well as the role of internal and external financial resources in the development of joint stock companies. The results of the research can be applied in the financial management practice of joint stock companies and may serve as a basis for further studies in the field of corporate finance and investment management.